Hybrid event bed characteristics and its role in high-frequency facies change of the Upper Triassic submarine fan in the West Qinling area of NE Tibetan Plateau. (December 2022) - Tan, Mingxuan; Sun, Haonan; Fu, Yilin; Zhang, Xu; Cui, Haonan; Ma, Haoran
Abstract: Hybrid event beds (HEBs) record disequilibrium in submarine fan evolution attributed to mud-forced dampening turbulence, which could be caused by allogenic and autogenic forcings in either the proximal or distal segment of a lobe-dominated submarine fan on several timescales. Detailed field investigation combined with petrographic and mineralogical analysis of selected outcrop samples indicate that the Upper Triassic submarine fan succession mainly comprises turbidites, HEBs, and debrites in the West Qinling (WQ) area of NE Tibetan Plateau. Five types of HEBs are recognized based on the thickness, sedimentary structure, and texture. Bed-by-bed description and measurement reveal that these HEBs show a distinct distribution pattern throughout the submarine fan succession, including dominance of HEB-1 and HEB-2 beds (∼71.50%) in distributary channel to lobe off-axis (FA1–FA3) and significant portion of HEB-3 to HEB-5 beds (∼54.22%) in lobe fringe to lobe distal fringe environments (FA4–FA5). Textural and petrographic characteristics of mudclasts suggest disaggregation of heterolithic, homogenous and less cohesive mudclasts (MC-1 to MC-4 type) within H1b and H3 interval of HEBs, which could play different roles in the longitudinal mud-driven flow transformation between turbulent and laminar flow behavior patterns. The vertical distributions of the HEB-prone succession are characterized by four types of depositional scenarios, which yields significant allogenic and autogenic signatures combined with the recognition of the dominant HEB types and thickening- or thinning-upward trend of the vertically stacked submarine lobes. This study can enhance our understandings of flow transformation of sediment gravity flows (SGF) along the eastern margin of the Paleo-Tethys Ocean based on the anatomy of several undiscovered deep-water outcrops, which were reflected by the initiation, gradual switching, and avulsion of the high-frequency submarine fan evolution during the Late Triassic. Highlights: HEBs are well developed both in proximal and distal parts of the submarine fan. Various types of mudclasts play different roles in the mud-driven transformation. Vertical distribution of HEBs records high-frequency change in the submarine fan.